Development of Open-Source Software for Repeatable Processing of Mechanical Test Data - Slater, Daniel (Department of Mechanical Engineering, 2024)
Experiments that test for the mechanical properties of materials typically generate large amounts of raw data that must be cleaned and processed before meaningful analysis can be performed. Manual processing of this data is often time-consuming and susceptible to errors. Furthermore, the necessary processing steps are usually similar for various datasets, given that mechanical testing procedures are standardised. These issues were addressed in this project through the development of a software toolkit for automated processing and repeatable analysis of mechanical test data. The toolkit, named Paramaterial, was developed as a pip installable Python package, and is designed for use in Jupyter Notebooks. The usage of Jupyter Notebooks makes the steps that a user took in processing and analysing data explicit, thus providing traceability and repeatability. The functionalities of Paramaterial were demonstrated by processing and analysing several datasets sourced from the literature and from the Centre for Material Engineering (CME) at the University of Cape Town (UCT). The example dataset gathered for the demonstrations consists of 100 uniaxial tensile tests, and 56 plane-strain tension tests on aluminium AA6061, as well as 70 uniaxial compression tests, and 40 plane-strain compression tests on aluminium AA3104. The Jupyter Notebooks containing the code for these demonstrations serve as tutorials for future users of the toolkit. Code documentation and user manuals have also been provided, making the software readily available to be used for improving the quality and quantity of processed experimental data in the field.